Morphology, anatomy, and mycorrhizal fungi colonization in roots of epiphytic orchids of Sempu Island, East Java, Indonesia - SITI NURFADILAH; NINA DWI YULIA; ESTI ENDAH ARIYANTI (Society for Indonesian Biodiversity, 2016)
Nurfadilah S, Yulia ND, Ariyanti EE. 2016. Morphology, anatomy, and mycorrhizal fungi colonisation in roots of epiphytic orchids of Sempu Island, East Java, Indonesia. Biodiversitas 17: 592-603. Roots of orchids have important role for survival, adaptation, water and nutrient absorption, and as a place of symbiosis with mycorrhizal fungi. The present study aimed to investigate the morphology, anatomy, and mycorrhizal status in roots of orchids of Sempu Island, Indonesia (Ascochilus emarginatus, Taeniophyllum biocellatum, and Thrixspermum subulatum), in relation to their adaptation to their habitat of coastal forests of Sempu Island. These orchids have different morphological characters; Ascochilus emarginatus and Thrixspermum subulatum are leafy orchids, while Taeniophyllum biocellatum is a leafless orchid. The results showed that all orchids have small number of velamen layers (1-2 layers) as an adaptation to the relatively humid condition. Cell wall thickenings of velamen, exodermis, and endodermis are structural adaptation of all orchids to the relatively high intensity of illumination, to reduce water loss because of transpiration. Mycorrhizal fungi colonization which is important for nutrient acquisition occurs in cortical cells. All orchids have differences in their cell shape, size, and specific characters, such as chloroplasts. The leafless Taeniophyllum biocellatum has many chloroplasts in the cortical root cells that support the photosynthesis process, while A. emarginatus and T. subulatum are lack of chloroplasts in their cortical root cells.